Guided Inquiry-Based Mathematics Module for Mathematical Critical Thinking Skills in Two Variable Linear Equation Systems (SPLDV) Materials (Tarbiyah Suska Conference Series, 2022)
This study was made to produce a valid, practical, and effective guided inquiry-based mathematics module for students' mathematical critical thinking skills. This module helps students to be an effective tool in critical thinking, especially on the material of the two-variable linear equation system (SPLDV). This type of research is research and development that refers to the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The types of data in this study are qualitative and quantitative data. The data collection instruments used were interview sheets, questionnaire sheets, and test questions (pretest-posttest) of mathematical critical thinking skills. The data analysis technique used is descriptive qualitative and quantitative descriptive analysis techniques. The data obtained from the validity questionnaire of educational technology experts and learning materials experts showed that the guided inquiry-based module produced based on the validity aspect met the very valid criteria with a validity percentage of 86.74%. The data obtained from the practical questionnaire based on guided inquiry on the SPLDV material shows that the developed module has met the very practical criteria. The data obtained from the effectiveness test of the mathematical critical thinking ability test were analyzed by inferential statistics, namely there were differences in the mathematical critical thinking abilities of class VIII students before and after using the module.
Keywords: mathematics module; guided inquiry; mathematical critical thinking skills